Kinetic theory and irreversible thermodynamics of dense fluids subject to an external field - Eu, Byung Chan (The Journal of chemical physics, 1987)
A formal theory of dense fluids subject to an external electric field is developed as an extension of the kinetic theory of dense fluids reported previously. The present formulation also refines and modifies the previous theory wherever deemed necessary and especially in the part related to the renormalization. The extended Gibbs relation and a theory of irreversible thermodynamics are developed. A generalized Kirkwood integral equation for correlation functions and a generalized equation for local nonequilibrium chemical potentials are also derived for nonequilibrium mixtures.